INDUCED ORDER STATISTICS AND THEIR CHARACTERIZATION FOR BIVARIATE KUMARSWAMY AND BIVARIATE PSEUDOKUMARSWAMY DISTRIBUTIONS - Sarita Singh (International Journal of Innovations in Engineering Research and Technology, 2014)
In this article two Bivariate distributions, namely, Bivariate Kumarswamy Distribution and Bivariate Pseudo-Kumaraswamy Distributions, as were derived from univariate Kumaraswamy Distribution and Pseudo-Kumaraswamy Distributions, have been considered. Using these Bivariate Distributions Induced Order Statistics have been obtained. Further, the probability density function of a single and joint induced statistics have been derived and to characterize them their moments and Entropy for order statistics have also been obtained.